The Application of the General Principles of Good Governance to Administrative Disputes in Public Service Digitalization Policies - Dila Nurul; Chandra Devaraihan Wahyudi; Yoyoh Yoyoh; Difky Maulana; Taufiq Alamsyah (Journal of Human Interaction and Social Studies, 2026)
This study examines the application of the General Principles of Good Governance in administrative disputes arising from public service digitalization policies in Indonesia. The research employs a non empirical normative legal method based on doctrinal legal inquiry and integrates statutory and conceptual approaches. The analysis focuses on the role of governance principles as normative standards for assessing the legality, accountability, transparency, and prudence of administrative decisions produced within digital public service systems. Primary legal materials include Law Number 30 of 2014 concerning Government Administration, Law Number 14 of 2008 concerning Public Information Disclosure, and Presidential Regulation Number 95 of 2018 concerning the Electronic Based Government System. The findings demonstrate that the General Principles of Good Governance remain applicable to electronic administrative decision making and function as essential safeguards against legal risks associated with algorithmic governance. The principle of prudence requires administrative authorities to maintain responsibility for decisions generated through digital systems, while the principle of openness supports transparency, auditability, and effective judicial scrutiny. The study concludes that administrative legality in the digital era depends not only on lawful outcomes but also on accountable and transparent decision making processes capable of ensuring effective legal protection and good governance.